(untitled) (Journal of Parents and Teachers, 2014)
In this issue of Padres y Maestros, it is offered an interview with Vera María Candau, professor of the Department of Education of the Catholic University of Rio de Janeiro. She gives her opinion about the current situation in Brazil, the importance of solidarity to create a different horizon, of globalization, and youth, among others.